Prednisone has no effect on the pharmacokinetics of CYP3A4 metabolized drugs – midazolam and odanacatib. (25th June 2014) - Marcantonio, Eugene E.; Ballard, Jeanine; Gibson, Christopher R.; Kassahun, Kelem; Palamanda, Jairam; Tang, Cuyue; Evers, Raymond; Liu, Chengcheng; Zajic, Stefan; Mahon, Chantal; Mostoller, Kate; Hreniuk, David; et al.
Abstract We evaluated the effect of prednisone on midazolam and odanacatib pharmacokinetics. In this open‐label, 2‐period crossover study in healthy male subjects, midazolam 2 mg was administered (Day −1) followed by odanacatib 50 mg (Day 1) during Part 1. In Period 2, prednisone 10 mg once daily (qd) was administered on Days 1–28; odanacatib was co‐administered on Day 14 and midazolam 2 mg was co‐administered on Days 1 and 28. Subjects were administered midazolam 2 mg on Days 42 and 56. Safety and tolerability were assessed throughout the study. A physiologically‐based pharmacokinetic (PBPK) model was also built. There were 15 subjects enrolled; mean age was 31 years. The odanacatib AUC0−∞ GMR (90% CI) [odanacatib + prednisone (Day 14, Period 2)/odanacatib alone (Day 1, Period 1] was 1.06 (0.96, 1.17). AUC0−∞ GMR (90%CI) [midazolam + prednisone (Day 28, Period 2)/midazolam alone (Day −1, Period 1] was 1.08 (0.93, 1.26). There were no serious AEs or AEs leading to discontinuation. PBPK modeling showed that prednisone does not cause significant effects on the exposure of sensitive CYP3A4 substrates in vivo at therapeutic doses. Co‐administration of prednisone 10 mg qd had no effect on pharmacokinetics of either odanacatib 10 mg or midazolam 2 mg.